2013
DOI: 10.1080/21553769.2014.901925
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of antimutagenic and antimitotic effects ofMorchella esculentaextracts and protocatechuic acid

Abstract: Morchella esculenta (L.) Pers. methanolic extracts, obtained from fruiting bodies growing wild in Serbia and Portugal, were screened for their antimutagenic properties and compared to protocatechuic acid, previously identified in both species. Salmonella typhimurium TA100 reversion assay was used for the antimutagenic properties. Methanolic extracts expressed important antimutagenic potency towards S. typhimurium, which was documented by index of antimutagenicity (I). A sample from Serbia expressed slightly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Protocatechuic acid or 3,4-dihydroxybenzoic acid (3,4-DHBA) is a catechol-type phenol present in some fruits and vegetables [1,2]. It has been shown that 3,4-DHBA displays antibacterial [3], antimutagenic [4], anti-inflammatory [5], antihyperglycemic [6] and highly antioxidant [7] effects. It also has potential applications for further microbiological synthesis of numerous valuable compounds, including the bioplastic precursor cis,cis-muconic acid [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Protocatechuic acid or 3,4-dihydroxybenzoic acid (3,4-DHBA) is a catechol-type phenol present in some fruits and vegetables [1,2]. It has been shown that 3,4-DHBA displays antibacterial [3], antimutagenic [4], anti-inflammatory [5], antihyperglycemic [6] and highly antioxidant [7] effects. It also has potential applications for further microbiological synthesis of numerous valuable compounds, including the bioplastic precursor cis,cis-muconic acid [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine showed mutagenic properties in cells but not in mammalians [ 91 ] and EFSA evaluated safe intake values [ 50 ], kaempferol also showed an absence of adverse effects [ 92 , 93 ]. For chlorogenic and caffeic acid [ 94 ] antimutagenic effects were found, and for protocatechuic acid [ 95 ] negative results of the mutagenic potential are available. For coffee itself, in summary, negative results were found [ 96 ] in animals, but not in the in vitro tests.…”
Section: Discussionmentioning
confidence: 99%